PELATIHAN PEMBUATAN KONTEN DIGITAL MARKETING DALAM MENINGKATKAN KOMPETENSI BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN EKONOMI STKIP PGRI JOMBANG - Diah Dinaloni; Henky Muktiadji; Cahyo Tri Atmojo (Yayasan Education and Social Center, 2023)
One of the strategies of the STKIP PGRI Jombang Economics Education Study Program to achieve the Prodi’s vision, mission and goals is to equip students with competence in the field of entrepreneurship. The rise of digital technology as a form of management change in the business wold cannot be utilized optimally by students. Digital marketing is one of the important aspects that must be mastered by economic actors today, this is because by using digital marketing products or services can be distributed at a faster rate and a wider reach than traditional marketing. If previously to gain market share, business people had to pick up the ball using a variety of effective marketing strategies, this time, only armed with digital marketing, it is easy to reach the market. To overcome the problems mentioned above, we carry out community service activities in the form of training on creating digital marketing content to improve student entrepreneurship competence, so that it is hoped that it will help training participants to understand more deeply about the most effective and efficient implementation of digital marketing, and be able to open up business opportunities, namely from business ideas to how to market it independently and sustainably. The method for implementing digital marketing content creation trained is dividen into three stages, namely, (1) The preparation stage, carried out to determine service goals, determine of training schedule. The community service targets are students from class of 2021 who have already taken entrepreneurship courses, while the venue is on the STKIP PGRI Jombang campus and the implementation time is Saturday April 15 2023 at 08.30 until finished; (2) Implementation stage, is the stage of training implementation where training participant are given training related to entrepreneurship and digital marketing as well as sharing opinions and providing assistance from the service team during group work; (3) Evaluation phase, which is carried out in the form of orientation on the results of the training participants by presenting their work in building content in the form of photos and video. During the presentation, each group received input regarding the content that had been created, so that participants could understand the procedures for creating digital marketing content that was interesting and easy for consumers to understand. From the evaluation results, 80% of the training participants understood and understood digital marketing materials and were able to implement digital marketing effectively and efficiently